Senescence markers in peripheral blood mononuclear cells in amnestic mild cognitive impairment and alzheimer’s disease - Salech, Felipe; San Martín, Carol D.; Concha Cerda, Jorge.; Romero Hernández, Esteban.; Ponce, Daniela P.; Liabeuf, Gianella; Rogers, Nicole K.; Murgas, Paola; Bruna, Bárbara; More, Jamileth; Behrens, Maria Isabel (MDPI, 2022)
Recent studies suggest that cellular senescence plays a role in Alzheimer’s Disease (AD) pathogenesis. We hypothesize that cellular senescence markers might be tracked in the peripheral tissues of AD patients. Senescence hallmarks, including altered metabolism, cell-cycle arrest, DNA damage response (DDR) and senescence secretory associated phenotype (SASP), were measured in peripheral blood mononuclear cells (PBMCs) of healthy controls (HC), amnestic mild cognitive impairment (aMCI) and AD patients. Senescence-associated βeta-galactosidase (SA-β-Gal) activity, G0-G1 phase cell-cycle arrest, p16 and p53 were analyzed by flow cytometry, while IL-6 and IL-8 mRNA were analyzed by qPCR, and phosphorylated H2A histone family member X (γH2AX) was analyzed by immunofluorescence. Senescent cells in the brain tissue were determined with lipofuscin staining. An increase in the number of senescent cells was observed in the frontal cortex and hippocampus of advanced AD patients. PBMCs of aMCI patients, but not in AD, showed increased SA-β-Gal compared with HCs. aMCI PBMCs also had increased IL-6 and IL8 mRNA expression and number of cells arrested at G0-G1, which were absent in AD. Instead, AD PBMCs had significantly increased p16 and p53 expression and decreased γH2Ax activity compared with HC. This study reports that several markers of cellular senescence can be measured in PBMCs of aMCI and AD patients.
Keywords: Peripheral blood mononuclear cells; aMCI; Alzheimer's disease; Aging; Cellular senescence